Adipocytokines are not associated with gestational diabetes mellitus but with pregnancy status. (July 2020) - Ebert, Thomas; Gebhardt, Claudia; Scholz, Markus; Schleinitz, Dorit; Blüher, Matthias; Stumvoll, Michael; Kovacs, Peter; Fasshauer, Mathias; Tönjes, Anke
Highlights: 5 out of 7 adipocytokines are dysregulated between pregnant and non-pregnant women. None of the adipocytokines significantly differed between GDM and non-GDM status. In partial least square discriminant analysis, insulin was most relevant for GDM. Chemerin and adiponectin were most relevant to discriminate pregnancy status. Pregnancy status but not presence of GDM can be distinguished by adipocytokines. Abstract: Aims: Adipose tissue-secreted proteins, i.e. adipocytokines, have been identified as potential mediators linking fat mass and adipose tissue dysfunction with impaired glucose homeostasis, alterations in the inflammatory status, and risk of diabetes. The aim of this study was to determine whether seven circulating adipocytokines are associated with gestational diabetes mellitus (GDM) or are altered by metabolic and weight changes during pregnancy itself. Methods: A panel of seven adipocytokines (i.e. adiponectin, adipocyte fatty acid-binding protein, chemerin, leptin, Pro-Enkephalin, progranulin, and Pro-Neurotensin) was quantified in serum in a cross-sectional cohort of 222 women with the following three groups matched for age and body mass index: (i) 74 pregnant women with GDM; (ii) 74 pregnant women without GDM; and (iii) 74 non-pregnant and healthy women. A stepwise statistical approach was used by performing pairwise comparisons, principal component analysis (PCA), and partial least square discriminant analysis (PLS-DA). Results: Five out of seven adipocytokines were dysregulated between pregnant and non-pregnant women, i.e. adiponectin, chemerin, leptin, Pro-Enkephalin, and progranulin. None of the adipocytokines significantly differed between GDM and non-GDM status during pregnancy. The same five adipocytokines clustered in a principal component representing pregnancy-induced effects. Fasting insulin was the most relevant parameter in the discrimination of GDM as compared to pregnant women without GDM, whereas chemerin and adiponectin were most relevant factors to discriminate pregnancy status. Conclusions: Pregnancy status but not presence of GDM can be distinguished by the seven investigated adipocytokines in discrimination analyses.